Particle Deposition Analysis Using DPM-DEM - A. Aziz N.; Zawawi M.H.; Zahari N.M.; Mazlan A.; Abas A.; Azman A.; Nashrudin M.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Erosion; Numerical methods; Coastal erosion; DEM; Discrete elements method; Discrete particle method-discrete element method; Discrete particle methods; DPM; Initial state; Particles depositions; Sand formations; Shoreline structures; Finite difference method